Transforming impact thinking into regenerative thinking: a Natura case study - Leão, Alexandre Arruda da Rocha (2024)
As a reference in sustainability, Natura is the subject of this case study, analyzed in light of impact thinking and articulating elements that enable economic gains to be achieved alongside environmental and social gains. The concept of regenerative economies and impact valuation through Integrated Profit and Loss (IP&L) is introduced in this context. From this overview, the following research question is posed: “How did the employment of management, valuation, and planning tools serve Natura in the journey from positive to regenerative impact?”. In addition to the main objective of “analyze how the utilization of management, planning, and evaluation tools can structurally enable regenerative impact, using Natura as a reference in sustainability and positive impact.” In this sense, the relevance of the research is established based on impact investments as strengtheners of the virtuous cycle of regeneration, while measuring the impact of activities on the environment and society optimizes the availability of different capitals. For this analysis, the case study was conducted through direct observation and participant observation to understand how Natura used MESA tools, strategic planning, and IP&L to transition from impact thinking to regenerative thinking at an organizational level, and a documentary analysis was also conducted consisting of Natura's corporate publications available to the public. With this done, it is analyzed how Natura appropriates these concepts and makes them visible in its culture and the application of tools, incorporating the idea of interbeing with nature and as nature (Wahl, 2016). Thus, this study offers a close look at the transformative potential of regenerative thinking in redefining sustainable business practices, promoting a change that goes beyond mitigating damages and achieves a proactive enhancement of the natural world and societal structures.